Opposition in Japan to the Olympics during the COVID-19 pandemic - Kato, T. (Humanities and Social Sciences Communications, 2021)
Little is known about the responses of citizens toward sporting mega-events held during a period of extended disasters, such as the 2020 Olympics held during the COVID-19 pandemic. This study aims to clarify the factors affecting citizens` attitudes by testing the following hypotheses: the perception of high cost, the burden on medical institutions, and high risk of infectious disease spread negatively affect attitudes, while the perception of pandemic countermeasures, economic benefits, and athletes positively affect attitudes. Based on an online survey of 800 citizens before the 2020 Olympics, the hypotheses were tested using logistic regression models with the extracted factors as the explanatory variables and the attitude toward the Olympics as the objective variable. The test results confirm the factors lineated by the hypotheses, except for the perception of high cost. The fear of a healthcare system collapse from the medical burden of dealing with an outbreak has an especially strong negative effect on the attitude toward the Olympics. These results have important implications for city governments and municipalities and suggest that they should not underestimate citizens` perceptions and attitudes when organizing mega-events and formulating proper communication. Further, the results may offer insights for the smooth strategic planning of large-scale events during unprecedented disasters.